2018
DOI: 10.1007/s00464-018-6465-9
|View full text |Cite
|
Sign up to set email alerts
|

Structured cost analysis of robotic TME resection for rectal cancer: a comparison between the da Vinci Si and Xi in a single surgeon’s experience

Abstract: The authors declare that no funding support was received for this study. Background Robotic-assisted surgery by the da Vinci Si appears to benefit rectal cancer surgery in selected patients, but still has some limitations, one of which is its high costs. Preliminary studies have indicated that the use of the new da Vinci Xi provides some added advantages, but their impact on cost is unknown. The aim of the present study is to compare surgical outcomes and costs of rectal cancer resection by the two platforms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…A single‐institute study from Korea found that total hospital charges were significantly higher for the robotic group (US$14 647 (€13 590; exchange rate 24 March 2020) versus US$9978 (€9260) respectively; P = 0·001), whereas the hospital profit was significantly lower (US$689 (€640) versus US$1671 (€1550); P < 0·001). Another group confirmed a significant reduction in costs with increasing surgeon experience and a fully robotic approach, especially with the da Vinci® Xi system compared with the da Vinci® Si™ robot.…”
Section: Discussionmentioning
confidence: 88%
“…A single‐institute study from Korea found that total hospital charges were significantly higher for the robotic group (US$14 647 (€13 590; exchange rate 24 March 2020) versus US$9978 (€9260) respectively; P = 0·001), whereas the hospital profit was significantly lower (US$689 (€640) versus US$1671 (€1550); P < 0·001). Another group confirmed a significant reduction in costs with increasing surgeon experience and a fully robotic approach, especially with the da Vinci® Xi system compared with the da Vinci® Si™ robot.…”
Section: Discussionmentioning
confidence: 88%
“…Also, the enhancements made in the Xi of simpler docking, laser guided port placement and boom-mounted robotic arms could have played a role in the faster times of draping and docking we found. Comparison to other studies is hard and unreliable due to unclearly described definitions of reported time frames [3,[12][13][14][15][16], different way of docking (three arms or single-port) [6,17,18], method of data collection and/or to retrospective study designs [3,[17][18][19]. Robot-assisted surgery, especially the phase before the surgeon starts behind the console, is a team effort.…”
Section: Discussionmentioning
confidence: 99%
“…Although robotassisted surgery has several advantages over conventional endoscopic surgery, its costs and prolonged operative times remain a subject of debate. High costs are not only ascribed to high purchase and maintenance costs of the robot, but to longer operating times as well [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The primary endpoint was operating time in two studies, 14 , 15 console time in one study 17 and was not reported in three studies 13 ,. 16 , 18 Exclusion criteria were T4 tumours in one study 16 and a history of other malignancies, signs of acute intestinal obstruction or perforation, familial adenomatous polyposis coli, hereditary nonpolyposis colorectal cancer and active inflammatory bowel disease in another study 15 . Four studies did not specify exclusion criteria, although they reported a consecutive cohort to be included 13 ,.…”
Section: Resultsmentioning
confidence: 99%